1998
DOI: 10.1007/s004840050078
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the CO 2 exchange rate of leaves of Ilex rotunda with elevated atmospheric CO 2 concentration in an urban canyon

Abstract: It was found that the atmospheric carbon dioxide (CO 2 ) concentration in an urban canyon in Fukuoka city, Japan during August 1997 was about 30 µmol mol −1 higher than that in the suburbs. When fully exposed to sunlight, in situ the rate of photosynthesis in single leaves of Ilex rotunda planted in the urban canyon was higher when the atmospheric CO 2 concentration was elevated. A biochemically based model was able to predict the in situ rate of photosynthesis well. The model also predicted an increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Repeated in summer, this experiment showed that high CO 2 concentration in the central core of Phoenix is a year-round phenomenon, although it is less intense in summer (Idso, Idso, and Balling 2001). Research in Nottingham, England, Vancouver, Canada, St. Louis, Missouri, New Orleans, Louisiana, Cincinnati, Ohio, and Fukuoka City, Japan confirms the existence of urban-rural differences in CO 2 levels, although those found in these studies were not as large as those found in Phoenix (Clarke and Faoro 1966;Colls 1990a, 1990b;Reid and Steyn 1997;Bakwin et al 1998;Takagi, Gyokusen, and Saito 1998).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Repeated in summer, this experiment showed that high CO 2 concentration in the central core of Phoenix is a year-round phenomenon, although it is less intense in summer (Idso, Idso, and Balling 2001). Research in Nottingham, England, Vancouver, Canada, St. Louis, Missouri, New Orleans, Louisiana, Cincinnati, Ohio, and Fukuoka City, Japan confirms the existence of urban-rural differences in CO 2 levels, although those found in these studies were not as large as those found in Phoenix (Clarke and Faoro 1966;Colls 1990a, 1990b;Reid and Steyn 1997;Bakwin et al 1998;Takagi, Gyokusen, and Saito 1998).…”
supporting
confidence: 56%
“…Clarke and Faoro (1966) reported diurnal CO 2 variations of 90 ppmv in Cincinnati, Ohio measured at 1 meter above the ground. In Fukuoka City, Japan, Takagi, Gyokusen, and Saito (1998) found CO 2 levels to be 30 ppmv higher in an urban canyon than in surrounding suburbs when measured at 2.5 m above ground. In an effort to assess timeof-day, seasonality, and height-of-measurement issues, Bakwin et al (1998) measured CO 2 mixing ratios on several large rural-based towers (measured at 610 m) in North Carolina and Wisconsin and found a strong diurnal pattern related to biological processes and the dynamics of the boundary layer.…”
Section: Urban Comentioning
confidence: 93%
“…Among these factors, CO2 concentration, air temperature and humidity might not be the same in the urban district and the control nursery. However, Takagi et al (1998) found that, in spite of having a higher CO2 concentration, the urban district caused reduced in situ photosynthetic rates in mature planted I. rotunda compared to the control nursery site due to lower air humidity.…”
Section: Discussionmentioning
confidence: 88%
“…Elevated CO 2 concentrations can increase NPP (Friedlingstein et al 1995). Urban CO 2 concentrations can be approximately 30% higher than rural CO 2 concentrations (Idso et al 2001), and even during the summer -when photosynthesis is maximized -urban CO 2 concentrations can exceed 450 ppm (Aikawa et al 1995, Takagi et al 1998, Gratani & Varone 2005. Soil-nitrogen levels can limit CO 2 fertilization of vegetation (Oren et al 2001), but soil nitrogen levels in urban areas may be sufficiently high to prevent this limitation from occurring.…”
Section: Potential Impacts Of Urbanization On Nepmentioning
confidence: 99%
“…Multiple studies have examined either atmospheric CO 2 concentrations or CO 2 fluxes (e.g. Aikawa et al 1995, Takagi et al 1998, Idso et al 2001, Takahashi et al 2001, Grimmond et al 2002, Nemitz et al 2002, Kuc et al 2003, Pataki et al 2003, Moriwaki & Kanda 2004, Gratani & Varone 2005 in urban areas. In addition, at least 2 studies (Milesi et al 2003, Imhoff et al 2004) have estimated the impacts of urbanization on NPP.…”
mentioning
confidence: 99%